Exosomes From Human Urine-Derived Stem Cells Encapsulated Into PLGA Nanoparticles for Therapy in Mice With Particulate Polyethylene-Induced Osteolysis - Li, Hui; Hu, Yihe; Zeng, Min; Yang, Junxiao; Fan, Xiaolei; Wang, Yinan; Xie, Jie (Frontiers in Medicine, 2021)
Background: Periprosthetic osteolysis is the primary reason for arthroplasty failure after total joint replacement because of the generation of wear particles and subsequent bone erosion around the prosthesis, which leads to aseptic loosening. Periprosthetic osteolysis is often treated with revision surgery because of the lack of effective therapeutic agents. As key messengers of intercellular interactions, exosomes can be independently used as therapeutic agents to promote tissue repair and regeneration. In this study, we fabricated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) that carry exosomes derived from human urine stem cells (USC-Exos) and explored their effects on polyethylene-induced osteolysis. Methods: USCs were identified by multipotent differentiation and flow cytometry analyses. 2 USC-Exos were isolated and identified by transmission electron microscopy (TEM), dynamic light scattering (DLS) and western blotting. PLGA microspheres containing USC-Exos were fabricated to synthesize NPs using the mechanical double-emulsion method. The obtained NPs were characterized in terms of stability, toxicity, exosome release and cell uptake. Then, these NPs were implanted into the murine air pouch model, and their effects on polyethylene-induced osteolysis were evaluated by microcomputed tomography (micro-CT) and histological analyses. Results: The average NP diameter was approximately 282 ± 0.4 nm, and the zeta potential was -2.02 ± 0.03 mV. After long-term storage at room temperature and 4 °C, the NP solution was stable without significant coaggregation. In vitro release profiles indicated sustained release of exosomes for 12 days. In vivo, injection of NPs into the murine air pouch caused less osteolysis than that of USC-Exos, and NPs significantly reduced bone absorption, as indicated by histology and micro-CT scanning. Conclusion: Our findings suggest that USC-Exo-based PLGA NPs can prevent particulate polyethylene-induced osteolysis and bone loss.